Respons Hidrologi Akibat Deforestasi di DAS Barito Hulu, Kalimantan Tengah - Moch. Anwar; Hidayat Pawitan; Kukuh Murtilaksono; I Nengah Surati Jaya (Institut Pertanian Bogor (IPB University), 2011)
The landcover change, particularly deforestation, can to affect of hydrological response on watershed.Deforestation of natural forest is identical to degradation of watershed functions, such as loos of land productivity due to increased soil erosion, runoff, evapotranspiration, and decreased of water storage. The main objective of this study is describes the hydrologic response on the Barito Hulu watershed due to landcover change (particularly deforestation) by the use Soil and Water Assessment Tool (SWAT) model. The result of the study showed that decreasing of forest area was 9.51% from initial condition can increase water yield, evapotranspiration, and erosion as much as 8.52%, 5.94%, and 1.73 t ha-1 year-1, respectively. Otherwise, water storage decreased as much as14.46%. The landcover on 1990 with rainfall 3,117.10 mm year-1 provided water yield of approximately 1,387.13 mm, evapotranspiration of 1,152.10 mm, water storage of 577.87 mm, and erosion of about 20.52 t ha-1 year-1. The landcover on 2003 with rainfall 2,613.2 mm year-1 provided water yield of approximately 1,385.50 mm, evapotranspiration of 1,121.10 mm, water storage of 106.60 mm, and erosion of about 33.15 t ha-1 year-1 with erosion tolerance of about 43.57 t ha-1 year-1.